2003
DOI: 10.1017/s0025315403008749
|View full text |Cite
|
Sign up to set email alerts
|

Pontobdella muricata and Trachelobdella lubrica (Hirudinea: Piscicolidae) on some marine fish in the Dardanelles, Turkey

Abstract: Fifteen individuals of four marine fish species (Torpedo marmorata, Raja clavata, Scorpaena porcus and Scorpaena scrofa) caught in the Dardanelles, Turkey, were examined for the leech Pontobdella muricata and Trachelobdella lubrica; 18 P. muricata and 23 T. lubrica were found on gills, at the base of the fins, and abdomen on 14 of the 15 fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 3 publications
4
15
1
Order By: Relevance
“…These parasite species, their sites of infections in the fish hosts, and their infection rates are shown in the Table. 3.1. Anoiktostoma coronatum (Wagner, 1852) Stossich, 1899 ( Figure 2) Body small (600-800 µm), oval to fusiform, oral sucker (100 × 120 µm) terminal, funnel-shaped, surrounded by a crown of large, sharp spines (number of spines [18][19][20]. Ventral sucker (50 × 55 µm) is small, circular, situated close to middle of body.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parasite species, their sites of infections in the fish hosts, and their infection rates are shown in the Table. 3.1. Anoiktostoma coronatum (Wagner, 1852) Stossich, 1899 ( Figure 2) Body small (600-800 µm), oval to fusiform, oral sucker (100 × 120 µm) terminal, funnel-shaped, surrounded by a crown of large, sharp spines (number of spines [18][19][20]. Ventral sucker (50 × 55 µm) is small, circular, situated close to middle of body.…”
Section: Resultsmentioning
confidence: 99%
“…This species is parasitic on many fish species and has been reported from various fish species of the families Serranidae, Sciaenidae, Scorpaenidae, etc. (18,19). Trachelobdella lubrica was recorded from Scorpaena spp.…”
Section: Longicollum Pagrosomimentioning
confidence: 99%
“…Meyer (1965) redescribed the species based on material from an unidentified serranid fish from western Africa, providing the best available taxonomic description for the species. Williams et al (1994) reported T. lubrica from fishes from the orders Elopiformes, Myctophormes and Perciformes in the Caribbean Sea, and Saglam et al (2003) and Sanver-Celik and Aydin (2006) reported T. lubrica from the Black Scorpionfish, Scorpaena porcus Linnaeus, 1758, and the Red Scorpionfish, Scorpaena scrofa Linnaeus, 1758, in the Dardanelles of the Aegean Sea. Trachelobdella lubrica was reported from lionfish from near Jacksonville, Florida (see Ruiz-Carus et al 2006, Bullard et al 2011), and Puerto Rico (Ramos-Ascherl et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…In Turkey, P. muricata was collected from the elasmobranchs including Torpedo marmorata and Raja clavata from the Aegean Sea, Raja sp. from the Marmara Sea, and R. clavata from the Black Sea (Ergüven and Candan 1992;Sağlam et al 2003;Öktener and Utevsky 2010).…”
Section: Received: March 2014mentioning
confidence: 99%
“…Pontobdella muricata (Linnaeus, 1758) causes local hemorrhages, swelling, tissue necrosis, and disappearance on the surface of epidermal tissue on its attachment regions on the host (Sağlam et al 2003;Bakopoulos and Ksida 2013).…”
mentioning
confidence: 99%